Bimetallic copper–vanadium mandelato complexes with bpy and phen as ancillary ligands. 51V NMR spectra of vanadates in DMSO. (15th July 2019) - Šimuneková, Mária; Schwendt, Peter; Gyepes, Róbert; Šimunek, Ján; Filo, Juraj; Bujdoš, Marek; Tatiersky, Jozef
Graphical abstract: Two heterometallic copper–vanadium complex [Cu( bpy )2 V2 O2 (O2 )2 ( R - mand )2 ][Cu( bpy )2 V2 O2 (O2 )2 ( S - mand )2 ]·2CH3 CN·2H2 O (1 ) and [Cu( phen )2 V2 O2 (O2 )2 ( R - mand )2 ][Cu( phen )2 V2 O2 (O2 )2 ( S - mand )2 ]·2CH3 CN·2H2 O (2 ), ( mand = mandelato(2–) = C6 H5 CH(O)CO2 2– ) were prepared and characterized by spectral methods and X-ray single crystal analysis. Abstract: Two novel heterometallic complexes [Cu( bpy )2 V2 O2 (O2 )2 ( R - mand )2 ][Cu( bpy )2 V2 O2 (O2 )2 ( S - mand )2 ]·2CH3 CN·2H2 O (1 ), and [Cu( phen )2 V2 O2 (O2 )2 ( R - mand )2 ][Cu( phen )2 V2 O2 (O2 )2 ( S - mand )2 ]·2CH3 CN·2H2 O (2 ), ( mand = mandelato(2–) = C6 H5 CH(O)CO2 2– ) were prepared and characterized by spectral methods. X-ray single-crystal analysis revealed the difference between both structures. While1 contains a bonding copper(II) and vanadium(V) atoms through the bridging oxygen atom Cu–O–V, the metallic atoms are connected in2 through the carboxylic group CuOCOV. Complexes1 and2 are immediately decomposed in their aqueous solutions, but their integrity is preserved for some time in DMSO. 51 V NMR spectra of DMSO solutions of vanadates(V), peroxidovanadates(V) and vanadium(V) mandelato complexes are presented for the first time.